Analisis Daya Saing Produk Agroindustri Subsektor Perkebunan dalam Perekonomian Wilayah Provinsi Jambi - Zulgani Zulgani; Syaparuddin Syaparuddin; Parmadi Parmadi (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2014)
This study aims to identify the potential competitiveness of the agro-industry sub-sector leading commodity plantations in Jambi Province. The long term goal of this research is obtained by a concrete formulation of the strategy of development of agro-industry sub-sector competitiveness leading commodity plantations integrated with the strategy of revitalizing the agricultural sector. The research method used was a secondary data analysis methods. This study was conducted over a period of two years. In the first year will be to identify potential agro industry leading commodity subsector mapping plantations and agro-industry plantation subsector superior product that has a high economic value, while the second year will be pursued to design the strategy and policy development of agro-industry commodity or superior products that possess the plantation sub-sector competitiveness and related to the realize the quality of economic growth and sustainable region. Keywords: agro-industry, the quality of economic growth, sustainable